Self-help housing as an effective delivery mechanism to reduce the backlog: research into self-help housing on state subsidised sites and services projects. - Ward, Mark (My University, 2022)
By announcing a radical shift away from formal housing provision to an approach of sites and services, the South African Department of Human Settlements has opened-up the potential for self-help housing to be re-established as a way for the poor to access land and housing. In view of the extensive housing shortages and historical rejection of incrementalism and the limited implementation of the Peoples’ Housing Process (PHP) in post-apartheid South Africa, the research has set-out to investigate whether self-help by way of sites and services is a viable option to address the backlog. By reviewing literature and evaluating the anonymous answers to questionnaires from officials and community members, the research has attempted to find out how the approach will be implemented. In getting a wider understanding of the proposed sites and services approach, the research has found that state-assisted self-help housing is an effective delivery mechanism that can help the poor to take control of their housing needs.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Urban Studies to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2023